The roles of vaspin, chemerin, and omentin in the determination of metabolic syndrome - Suliga, Edyta; Wawszczak, Monika; Gluszek, Stanislaw (Medical Studies/Studia Medyczne, 2018)
Metabolic syndrome (MetS) is defined as multiple risk factors including abdominal obesity, dyslipidaemia, abnormal glycaemia, and elevated blood pressure. The incidence of MetS and pathophysiological mechanisms underlying its development are still not fully understood. It is thought that the occurrence of MetS arises from the complex relationship between genetic and environmental factors. The aim of the study was to overview and summarise current knowledge regarding genetic determinants of MetS. Also analysed were the relationship between polymorphisms of the genes encoding selected adipokines (vaspin, chemerin, omentin) and the risk of MetS, as well as other metabolic disorders. The precise determination of MetS genotype is difficult because metabolic syndrome occurrence is a combination of multiple risk factors. A thorough understanding of pathomechanisms of MetS, involving selected adipokines, may in the future allow the use of these adipokines as potential biomarkers of metabolic disorder risk.